Alterations in leukocyte DNA methylome are associated to immunosuppression in severe clinical phenotypes of septic patients - Beltrán-García, Jesús; Casabó-Vallés, Germán; Osca-Verdegal, Rebeca; Navarrete-López, Paula; Rodriguez-Gimillo, María; Nacher-Sendra, Elena; Ferrando-Sánchez, Carolina; García-López, Eva; Pallardó, Federico V.; Carbonell, Nieves; Mena-Mollá, Salvador; García-Giménez, José Luis (Frontiers in Immunology, 2024)
Sepsis patients experience a complex interplay of host pro- and anti-inflammatory processes which can compromise outcome. Even taking the latest clinical and scientific research data into account, the immunosuppressive events occurring during a septic episode are incompletely understood. Moreover, there is a lack of data on the way epigenetics can modulate immunosuppression, which in turn affects patient survival. To advance current understanding of the mechanisms underlying immunosuppression, in this study we explored DNA methylation changes using the Infinium MethylationEPIC v1.0 BeadChip Kit in leukocytes from patients suffering from sepsis, septic shock, and critically ill patients as controls, within the first 24 h after admission in the Intensive Care Unit of a tertiary hospital. The top 100 differentially methylated positions (DMPs) between septic shock and critically ill patients enabled us to clearly distinguish between the 3 groups of patients. Interestingly, the top 6,657 DMPs were associated with organ dysfunction and lactate levels. Two different analysis approaches (based on the use of DMRcate and mCSEA) comparing septic shock and critically ill patients revealed a total of 1,256 differentially methylated regions (DMRs) involved in critical immune system-related pathways. Among the individual genes exhibiting significant differential methylation, IL10, TREM1, IL1B, and TNFAIP8 showed the largest methylation differences among the different groups when analyzing their methylation levels by DNA bisulfite pyrosequencing. Our findings indicate that DNA methylation profile undergoes the most substantial changes in patients with septic shock, and that these changes are linked to disease severity. Importantly, IL10 and S100A8, which are closely related to immunosuppression, were hypomethylated in septic shock patients.